2022
DOI: 10.3390/antiox11101859
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NRF2 Sensitizes Esophageal Adenocarcinoma Cells to Cisplatin through Induction of Ferroptosis and Apoptosis

Abstract: Esophageal adenocarcinoma (EAC), the predominant type of esophageal cancer in the United States, develops through Barrett’s esophagus (BE)-dysplasia-carcinoma cascade. Gastroesophageal reflux disease, where acidic bile salts refluxate into the esophagus, is the main risk factor for the development of BE and its progression to EAC. The NFE2-related factor 2 (NRF2) is the master cellular antioxidant regulator. We detected high NRF2 protein levels in the EAC cell lines and primary tissues. Knockdown of NRF2 signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In addition, realgar (REA), a Chinese herbal decoction, was found to not only decrease the proliferation, migration and invasion of KYSE150 and Eca109 cells but also promote ferroptosis by activating the ROS-ASK1-p38 MAPK signaling pathway [233]. Moreover, high expression of NRF2 protein in both primary tissues and EAC cell lines was detected by Ballout et al, and further studies showed that treatment with the NRF2 inhibitor brusatol alone or in combination with cisplatin induced ferroptosis of EAC cells by targeting NRF2; these results were evidenced by reduced expression of the ferroptosis markers GPX4 and xCT, which was confirmed in vivo [234]. Furthermore, analyses revealed that stearoyl-CoA desaturase (SCD1) conferred radiation resistance by inhibiting ferroptosis in ESCC cells and was related to unfavorable survival in patients with ESCC.…”
Section: Targeting Other Factors Related To Ferroptosismentioning
confidence: 86%
“…In addition, realgar (REA), a Chinese herbal decoction, was found to not only decrease the proliferation, migration and invasion of KYSE150 and Eca109 cells but also promote ferroptosis by activating the ROS-ASK1-p38 MAPK signaling pathway [233]. Moreover, high expression of NRF2 protein in both primary tissues and EAC cell lines was detected by Ballout et al, and further studies showed that treatment with the NRF2 inhibitor brusatol alone or in combination with cisplatin induced ferroptosis of EAC cells by targeting NRF2; these results were evidenced by reduced expression of the ferroptosis markers GPX4 and xCT, which was confirmed in vivo [234]. Furthermore, analyses revealed that stearoyl-CoA desaturase (SCD1) conferred radiation resistance by inhibiting ferroptosis in ESCC cells and was related to unfavorable survival in patients with ESCC.…”
Section: Targeting Other Factors Related To Ferroptosismentioning
confidence: 86%
“…NRF2 silencing or pharmacological inhibition by brusatol reduced the proliferation and migration of breast cancer (BC) cells, inhibited proliferation, activated apoptosis, sensitized BC cells to cisplatin in vitro, and slowed tumor cell growth in vivo [ 59 ]. Along these lines, esophageal adenocarcinoma (EAC) displayed increased NRF2, and both the knockdown of NRF2 and pharmacological inhibition with brusatol inhibited tumor growth by inducing ferroptosis and apoptosis [ 60 ]. In the case of metastatic Ewing sarcoma and osteosarcoma, it has been described that oxidative stress attenuates metastasis; here, treatment with the class-I HDAC inhibitor MS-275 inhibited the deacetylation of YB-1 (Y-box binding protein 1), reduced its binding to the 5’UTR of NFE2L2 , reduced the translation of NRF2, and increased the levels of intracellular ROS [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combined multi-pathway inhibition of ferroptosis evasion mechanisms should be sought to ensure that ferroptosis can occur successfully. Second, drugs such as Sorafenib and Brusatol have been validated as effective inducers of ferroptosis in some cancers ( Tang et al, 2023 ; Ballout et al, 2022 ); however, they do not cause AML cell death by inducing ferroptosis, and it is necessary to dig deeper into the mechanism of the inability of ferroptosis to occur with these drugs, and to carry out a systematic ferroptosis study for AML. Third, there are interactions between ferroptosis and other cell death pathways, such as ferritin degradation associated with autophagy, increased iron and ROS levels ( Hou et al, 2016 ), and the activation of excess ROS, which may cause cellular autophagy and chemotherapy resistance ( Gu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%